PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MENGHARGAI KERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONESIA PADA PEMBELAJARAN IPS KELAS V SDN CIJATI - Intan Talitha, Rahma; Cempaka Sari, Tiara (STKIP Subang, 2016)
This study aims to improve understanding of the concept of students in respect of material diversity of tribes and cultures in Indonesia in class V SDN Cijati by applying Role Playing. Based on the lack of understanding of students during the learning takes place so that the study of students is less satisfactory. This study uses a Class Action Research (PTK) with system cycle of planning, implementation, observation and reflection. This research was conducted in two cycles of the techniques used in this study is a technique tests, questionnaires and observations. Assessment Rubric RPP RPP using the first cycle has a percentage of 95% and cycle II has pesentase 100% results. Observation sheet IPS implementation of learning by using role playing in the first cycle has pesentase 96.3% and cycle II has pesentase 100% results. The results of post-test students who complete the first cycle has a percentage of 70%, while incomplete 30%, while the post-test results of students in the second cycle is finished to have a percentage of 100%. The result of understanding the concept of learners who complete the first cycle has pesentase 87%, while the result of understanding the concept of the second cycle which has pesentase 100% complete. Application of the method Role Playing very supportive towards the understanding of the concept of cherishing diversity of tribes and cultures in Indonesia, especially in primary schools Cijati. This is due to the application of methods Role Playing educators must be more active in learning, can accept ethnic and cultural diversity, as well as to develop social skills.